Daya Dukung Kesiapan E Retribusi Pasar Blambangan Kabupaten Banyuwangi ( Supporting Capac ity of E Retribution Readiness in Blambangan Market Banyuwangi Regency) - Novitasari, Dessy; Hidayat, Rachmat; Azhari, Abdul Kholiq (e-Sospol, 2019)
AbstractThis study aims to describethe supporting capacity of E Retribution readiness in Blambangan Market. Thisresearch was based on the existingrenewal information technology wi th the development of e Governmentregarding the acceptance and collection of electronic market retribution or Market E Retribution. It is heldby the Department of Industry and Trade of Banyuwangi Regency in collaboration with PT Bank Jatim as afacilitat or of supporting infrastructure for the implementation of Market E Retribution. To know about thereadiness of implementing E Market Retribution, there are three elements of e Government success inimplementing Market E Retribution, namely support, capacit y, and value. Therefore, this descriptive studyemployed a qualitative approach. Research data were collected through observation, documentation, andinterview. The informants were determined purposively. To test data validity, researchers used triangulati ontechnique. Then, the data were analyzed by systematically compiling data obtained from interview, fieldnote, and other sources; so that, the data were easily understood and the findings can be informed to thepeople. The findings indicated that the rea diness of E Retribution implementation in Blambangan marketwas shown from some elements. Support element as the first element produced the implementation of theMarket E Retribution policy through the collaboration of the Department of Industry and Trade with PTBank Jatim. The second element was capacity. It produced the infrastructure used in the implementationofMarket E Retribution. The transaction tool used was an EDC (Electronic Data Capture) machine. Thefinal element was value which wasin the form of evaluation on the MarketE Retribution program by tradersto the implementer of Market E Retribution. The usefulness value of E Retribution in Blambangan Marketchanged the mindset of traders regarding the ease of information technology in public servi ces. Moreover,it could be felt directly such as in the implementation of E Market Retribution. The value obtained in thepresence of this Market E Retribution was certainty. Count certainty, deposit certainty, and merchantcertainty in receiving the retri bution were e Government based services.Keywordss upporting capacity, e government, market e retribution